Neuroprotection and immunomodulation following intraspinal axotomy of motoneurons by treatment with adult mesenchymal stem cells - Spejo, A. B.; Chiarotto, G. B.; Ferreira, A. D.F.; Gomes, D. A.; Ferreira, R. S. [UNESP]; Barraviera, B. [UNESP]; Oliveira, A. L.R. (Springer Nature, 2018)
Background: Treatment of spinal cord injury is dependent on neuronal survival, appropriate synaptic circuit preservation, and inflammatory environment management. In this sense, mesenchymal stem cell (MSC) therapy is a promising tool that can reduce glial reaction and provide trophic factors to lesioned neurons. Methods: Lewis adult female rats were submitted to a unilateral ventral funiculus cut at the spinal levels L4, L5, and L6. The animals were divided into the following groups: IA (intramedullary axotomy), IA + DMEM (Dulbecco's modified Eagle's medium), IA + FS (fibrin sealant), IA + MSC (106 cells), and IA + FS + MSC (106 cells). Seven days after injury, qPCR (n = 5) was performed to assess gene expression of VEGF, BDNF, iNOS2, arginase-1, TNF-α, IL-1β, IL-6, IL-10, IL-4, IL-13, and TGF-β. The cellular infiltrate at the lesion site was analyzed by hematoxylin-eosin (HE) staining and immunohistochemistry (IH) for Iba1 (microglia and macrophage marker) and arginase-1. Fourteen days after injury, spinal alpha motor neurons (MNs), evidenced by Nissl staining (n = 5), were counted. For the analysis of astrogliosis in spinal lamina IX and synaptic detachment around lesioned motor neurons (GAP-43-positive cells), anti-GFAP and anti-synaptophysin immunohistochemistry (n = 5) was performed, respectively. Twenty-eight days after IA, the gait of the animals was evaluated by the walking track test (CatWalk; n = 7). Results: The site of injury displayed strong monocyte infiltration, containing arginase-1-expressing macrophages. The FS-treated group showed upregulation of iNOS2, arginase-1, proinflammatory cytokine (TNF-α and IL-1β), and antiinflammatory cytokine (IL-10, IL-4, and IL-13) expression. Thus, FS enhanced early macrophage recruitment and proinflammatory cytokine expression, which accelerated inflammation. Rats treated with MSCs displayed high BDNF-positive immunolabeling, suggesting local delivery of this neurotrophin to lesioned motoneurons. This BDNF expression may have contributed to the increased neuronal survival and synapse preservation and decreased astrogliosis observed 14 days after injury. At 28 days after lesion, gait recovery was significantly improved in MSC-treated animals compared to that in the other groups. Conclusions: Overall, the present data demonstrate that MSC therapy is neuroprotective and, when associated with a FS, shifts the immune response to a proinflammatory profile.
Keywords: Astrogliosis; Funiculus cut; Immunomodulation; Microglial reaction; Motoneuron; Spinal cord